The Federal Democratic Republic of Ethiopia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context: Ethiopia's investment-led development strategy has delivered robust growth and progress toward Millennium Development Goals (MDGs). Restrained fiscal and monetary policies have helped maintain macroeconomic stability, although the financing mode of the continuing large-scale investment through public enterprises could risk undermining macroeconomic stability. A cautious policy stance will be critical in preserving the recent gains. Focus of the consultation: The discussions centered on policies to sustain strong economic growth and promote structural transformation. Issues covered included: (i) the policy mix to preserve macroeconomic stability and debt sustainability; (ii) the public sector investment program and its financing; and (iii) financial deepening, export competitiveness and the business climate. Outlook and Risks: Growth is expected to remain strong, driven mainly by agriculture and services. Inflation should continue to remain in single digits, in line with a tight monetary policy. Key downside risks include insufficient financing for infrastructure investment in the Growth and Transformation Plan (GTP), lower prices of main export commodities, and weather-related shocks, particularly a drought. Policy mix: Staff recommendations focused on sustaining a cautious policy stance, prioritization of public investments and closer monitoring of state-owned enterprises to ensure prudent borrowing in the context of a medium-term debt management strategy, enhancing export competitiveness, greater resource mobilization and development of the financial sector, and a more prominent role for the private sector. Structural improvements in the functioning of the money and foreign exchange market and building foreign reserves to at least three months of imports were suggested to enhance resiliency. The need for greater interest rate and exchange rate flexibility and improved competitiveness of the traded goods sector, including through exchange rate adjustment, was underscored.